Effectiveness and Strategy Policy of Micro Business License Through Online - Handoyo, Arif Yoga; Rahman, Yozi Aulia (Universitas Negeri Semarang, 2020)
The government of Semarang city has established a licensing service that is based online for micro and Small business license of micro Enterprise through Online or i-Jus Melon in realizing the improvement of public service quality and increased number of micro-enterprises And small in Semarang city, but in the implementation is still found some obstacles and in the year 2018 decreased the number of micro and small businesses. The research aims to analyse (1) micro and small business profiles in Semarang city, (2) the level of effectiveness of i-Jus Melon, (3) The development strategy of i-Jus Melon. The data analysis technique used is a descriptive percentage analysis and Analytical Hierarchy Process (AHP). The results show that implementation of the policy of i-Jus Melon on micro and small business in Semarang city has been running quite effectively with the result of effectiveness calculation of 68.3 percent. The priority order of the first i-Jus Melon policy development strategy was the government's policy of 40 percent in value, the second was the construction weighing a value of 35.3 percent, and the third was a partnership with value weights of 24.8 percent. Pemerintah kota Semarang telah membentuk layanan perizinan yang berbasis online untuk usaha mikro dan kecil dari Usaha Mikro melalui Online atau i-Jus Melon dalam mewujudkan peningkatan kualitas layanan publik dan peningkatan jumlah usaha mikro dan kecil di kota Semarang , namun dalam implementasinya masih ditemukan beberapa kendala dan pada tahun 2018 menurun jumlah usaha mikro dan kecil. Penelitian ini bertujuan untuk menganalisis (1) profil usaha mikro dan kecil di kota Semarang, (2) tingkat efektivitas i-Jus Melon, (3) Strategi pengembangan i-Jus Melon. Teknik analisis data yang digunakan adalah analisis persentase deskriptif dan Analytical Hierarchy Process (AHP). Hasil penelitian menunjukkan bahwa implementasi kebijakan i-Jus Melon pada usaha mikro dan kecil di kota Semarang telah berjalan cukup efektif dengan hasil perhitungan efektivitas 68,3 persen. Urutan prioritas strategi pengembangan kebijakan i-Jus Melon pertama adalah kebijakan pemerintah yang nilainya 40 persen, yang kedua adalah konstruksi dengan bobot 35,3 persen, dan yang ketiga adalah kemitraan dengan bobot nilai 24,8 persen.